Quality Characteristics of Functional Pork Sausages Incorporated with Oat Bran Powder - Jandyal, Mehak; Malav, O. P.; Mehta, Nitin; Wagh, Rajesh V. (Journal of Meat Science, 2022)
Sausages were developed by replacing lean meat with oat bran (OB) at 3%, 6%, and 9% levels. pH, cooking yield, instrumental textural profile and sensory properties of treated sausages were evaluated. Different levels of dietary fiber source with very good sensory acceptability were compared with control. Overall acceptability of 6 per cent fibre (oat bran) incorporated sausages were comparable with control. The moisture level of all treatment sausages dropped significantly (P
Keywords: Oat bran; Powder, Functional; Pork sausages; Quality